ISU AKTUAL DAKWAH DALAM STUDI ISLAM - Santoso, Budi; Alpian, Alpian; Normal, Normal; Mila, Nurul (Asosiasi Dosen PTKIS Indonesia, 2024)
The more sophisticated technological developments are, it must also be accompanied by the strengthening of mental conditions and faith so that they are not easily eroded in behavior that deviates from the teachings of Islamic law. The sophistication of communication tools used today, which can connect people from one part of the world to another opens up great opportunities for information exchange, friendship and friendship between people with various different backgrounds, various ethnicities and different religions. Thus, the issue of da'wah has an important meaning in life so that the issue of extreme da'wah (radicalism) should be avoided and take the middle path (al-wasath) of da'wah that is humanist, polite and not extreme better so that the goal of dakawah is achieved properly. Then regarding the pros and cons of LGBT: LGBT support groups must be addressed with a sense of responsibility, must not be intimidated or even persecuted, so for groups that reject LGBT, they should constantly give a touch of humanist-religious accusations in accordance with religious norms. Furthermore, this article, explains that a good and critical moral attitude is highly expected to dismiss all da'wah issues that develop, the key is to the dai ruler as the spearhead of da'wah al-wasath who is humanist, polite and not extreme, so that the goal of da'wah is well achieved.